What Factors Influence Clinicians' Use of Technology in Neurorehabilitation? A Multisite Qualitative Study. Issue 5 (30th January 2021) - Bower, Kelly J; Verdonck, Michele; Hamilton, Anita; Williams, Gavin; Tan, Dawn; Clark, Ross A
Abstract: Objective: Technology is being increasingly used for physical assessment and interventions in health care settings. However, clinical adoption is relatively slow, and the factors affecting use remain underexplored. This study aimed to investigate factors influencing technology use by clinicians working in neurorehabilitation. Methods: In this qualitative study, 9 physical therapists and 9 occupational therapists (N = 18) were recruited from urban and regional locations in Australia and in Singapore. Three 60-minute focus groups were conducted via video conferencing. Each group comprised 3 physical therapists and 3 occupational therapists working across different neurorehabilitation settings. Participants were asked to discuss which technologies they used in their workplace for physical assessment and treatment and barriers, motivators, and future desires for technology use. Transcripts were analyzed independently using an inductive approach to generate codes and themes. Results: Our results comprised 3 themes and 7 categories. These were encompassed by a single overarching theme, namely "Technology use is influenced by the benefits and challenges of the technology itself, users, and organizational context." Themes showed that technology should promote effective interventions, is preferred if easy to use, and should be dependable. Furthermore, clinical reasoning is important, and users have varying levels of receptivity and confidence in technology use. Also, organizational resources are required, along with supportive cultures and processes, to facilitate technology use. Conclusions: The themes identified multiple and interlinking factors influencing clinicians' use of technology in neurorehabilitation settings. Clinicians often consider context-specific benefits and challenges when deciding whether to use technology. Although our study found that clinicians generally perceived technology as having a beneficial role in improving health outcomes, there were several challenges raised. Therefore, the characteristics of the technology itself, individual users, and organizational context should be considered. Impact: These findings will guide successful technology implementation and future developments.